1998
DOI: 10.1016/s0029-7844(98)00079-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy After Radical Hysterectomy for Cervical Carcinoma: A Comparison With Effects of Adjuvant Radiotherapy

Abstract: The use of adjuvant chemotherapy reduces extrapelvic recurrences. The combination of both adjuvant therapies may improve the prognosis for high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 17 publications
0
46
0
1
Order By: Relevance
“…Concurrent chemoradiotherapy and LRH have recently been regarded as the standard of treatment for high risk tumors [32,33,34,35]. Evidence exists for the use of cisplatin based combination chemotherapy to improve overall survival in women with advanced cervical cancers [36,37,38,39,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent chemoradiotherapy and LRH have recently been regarded as the standard of treatment for high risk tumors [32,33,34,35]. Evidence exists for the use of cisplatin based combination chemotherapy to improve overall survival in women with advanced cervical cancers [36,37,38,39,40,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists for the use of cisplatin based combination chemotherapy to improve overall survival in women with advanced cervical cancers [36,37,38,39,40,41,42]. Experiences with neoadjuvant chemotherapy for poor risk cervical carcinomas suggested that cisplatin-based combination chemotherapy was effective not only in local tumor and may also reduce the incidence of lymph node metastasis and even eradicate microscopic metastasis in distant organs [32,33,34]. However, in contrast to these results, Katsumata et al reported a randomized, controlled study of stage Ib2-IIb cervical cancer, which showed no significant difference between a NAC-combined surgery group and the surgery alone group in terms of resection and survival rate [43].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, since 6 of 10 recurrences in RH + RT patients occurred at distant sites, the role of adjuvant chemotherapy should be prospectively investigated even in patients with negative lymph node metastasis. In terms of improvement in survival, it may be worthwhile to consider new strategies, such as chemotherapy combined with radiation [17], and adjuvant concurrent chemoradiation [18,19] for the high-risk patients. In this respect, promising results have been achieved with concurrent chemoradiation [18,19] and combination chemotherapy with paclitaxel and cisplatin in patients with advanced or recurrent disease [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested that adjuvant chemotherapy increased the survival rate of high-risk patients; however, a randomized trial showed no clear consensus [22]. Iwasaka et al [17] suggested in their study that the use of adjuvant chemotherapy with a combination of CDDP, vincristine, mitomycin C, and peplomycin, reduces extrapelvic recurrences and, considering the pattern of recurrences, a combination of both chemotherapy and radiotherapy may improve the prognosis further for high-risk patients. Although these strategies still do not have consensus even for the patients with positive lymph nodes in an adjuvant setting, it may be necessary to develop new strategies for the selected lymph node-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue to take into consideration is that, in several studies, which directly compared adjuvant RT to adjuvant CT, it has been demonstrated a different distribution of the site of recurrence, with an estimated higher rate of distant metastases in patients treated with radiotherapy (range 14-71%), compared to those submitted to chemotherapy (range 8-23%), whom, otherwise, experienced a higher rate of local recurrence (8-85% respect to 14-38%) [19,20,31]. Once again, our data are comparable with these above, in fact we have recorded in most cases a locoregional recurrence with an overall rate of 13.3%.…”
Section: Accepted Manuscriptmentioning
confidence: 99%